Breaking barriers towards credible research: Outcomes of a workshop at the BNA Festival of Neuroscience 2025 - Weinerova, Josefina; Tibon, Roni; Bast, Tobias; Grasmeder Allen, Rachel (Brain and neuroscience advances, 2025)
Understanding the specific barriers and possible solutions to credible research for early career researchers is key to enabling the next generation of scientists to implement these practices. Here we describe the outcomes of a workshop that tackled these issues, held at the BNA Festival of Neuroscience 2025. Workshop attendees highlighted various challenges to credible research that are highly relevant for early career researchers. In particular, time constraints were highlighted as a universal barrier across multiple credible research practices, and attitudes of more senior researchers/supervisors were perceived as an important challenge. Participants also highlighted solutions to help implement credible research that can be pursued by individual researchers, but, importantly, also emphasised the importance of “structural” solutions, requiring initiative by stakeholders, including academic institutions, journals and funders. We hope the summary of the workshop will foster active debate on the topic within the neuroscience community.